Simazine degradation in agroecosystems: Will it be affected by the type and amount of microplastic pollution?. (15th March 2022) - Zhou, Jie; Wen, Yuan; Cheng, Hongguang; Zang, Huadong; Jones, Davey L.
Abstract: Plastics and herbicides represent two of the most extensive and persistent anthropogenic contaminants entering agroecosystems. The synergistic interaction of these pollutants on soil health, however, remains poorly understood. For the first time, we investigated the behavior of a common selective triazine herbicide (simazine) in soil containing 0%, 1%, 5%, 10%, and 20% (w/w) of two commonly found microplastics, namely polyethylene (PE) and polyvinyl chloride (PVC). The mineralization of 14 C‐labeled simazine in soil decreased with the presence of both PE and PVC as indicated by the lower total 14 CO2 loss. Consequently, the half‐life of simazine increased in the presence of microplastics, although there was little difference between microplastic types. The ratio of fungi‐to‐bacteria in the soil increased by 9%–18% after 1% of microplastics addition, while enzyme activities involved in C‐cycling decreased by 20%–46% in soil amended with PVC relative to the control. Further, enzyme activities were negatively correlated with the half‐life of simazine when added with PVC. Therefore, we ascribe the repression in simazine degradation to changes in microbial community structure (increased fungi‐to‐bacteria ratio) and reduced enzyme activities. Overall, microplastics accumulation in soil decreases herbicide breakdown resulting in herbicide residuals remaining, which in turn, may increase their risk of reaching ground or surface waters.